A Meta-Analysis of Single-Subject Research on Behavioral Momentum to Enhance Success in Students with Autism - Cowan, Richard J.; Abel, Leah; Candel, Lindsay (Journal of autism and developmental disorders, 2017)
We conducted a meta-analysis of single-subject research studies investigating the effectiveness of antecedent strategies grounded in behavioral momentum for improving compliance and on-task performance for students with autism. First, we assessed the research rigor of those studies meeting our inclusionary criteria. Next, in order to apply a universal metric to help determine the effectiveness of this category of antecedent strategies investigated via single-subject research methods, we calculated effect sizes via omnibus improvement rate differences (IRDs). Outcomes provide additional support for behavioral momentum, especially interventions incorporating the high-probability command sequence. Implications for research and practice are discussed, including the consideration of how single-subject research is systematically reviewed to assess the rigor of studies and assist in determining overall intervention effectiveness .